(untitled) (Bangladesh Critical Care Journal, 2024)
Background: Pelvic fracture urethral distraction defect is a traumatic injury to the male urethra that affects the region between the bulbar urethra and the prostatic apex. Pelvic fracture causes urethral injury in about 10% of patients. Combined retrograde urethrogram and antegrade cystourethrogram is used to define the length of the urethral injury before planning the definitive surgery. But during antegrade cystourethrogram bladder outlet sometimes fails to open due to faulty technique, prolong suprapubic catheterization and increase sympathetic drive, leading to erroneous estimation of the length of urethral injury. To overcome this problem Silodosin used in this study, which is a highly uroselective and rapid-acting α-adrenoreceptor antagonist in comparison to other α-adrenoreceptor antagonists available in the market. The uroselectivity of Silodosin helps in maximizing the effect by opening the bladder outlet and limiting the adverse effect on the cardiovascular system.The objective of the study was to assess the effectiveness of Silodosin in opening bladder outlet in patients with pelvic fracture urethral distraction defect on antegrade cystourethrogram. Methods: This is a Quasi-experimental study that was conducted in the Department of Urology, Bangabandhu Sheikh Mujib Medical University. In this study, 35 Patients with pelvic fracture urethral distraction defect with suprapubic catheter in situ who failed to open the bladder outlet on initial antegrade cystourethrogram were included. Urine culture and sensitivity report is confirmed negative. All participants were received a single dose of Silodosin capsule 3 hours before the antegrade cystourethrogram. Retrograde urethrogram was performed. After 3 hours bladder was filled with diluted contrast through the indwelling suprapubic catheter under sterile conditions according to bladder capacity. When the participants were felt the normal desire to void, bladder filling was stopped and voiding command was given and x-ray films were taken. Then the x-ray films were reviewed and findings were noted about the opening of the bladder outlet and visualization of the posterior urethra. Any complications during the procedure were observed and noted. After confirming hemodynamic stability, patients were advised to go home and continue the prescribed antibiotic for 5 days. Results: Thirty-five men were evaluated during this study period. The mean ages of the patients were 39.9±10.4 years. All patients had a suprapubic catheter in situ and the mean duration of the suprapubic catheter was 3.8 ± 1.5 months. On average 363±87.3 ml of diluted contrast were introduced to initiate voiding reflex. Thirty-two patients out of the 35 patients (91.4%) were able to achieve the satisfactory opening of the bladder outlet (95% confidence interval 82.11- 100%), while 3 patients (8.6%) failed to open the bladder outlet. No patient developed postural hypotension after single dose of Silodosin. Two patients were reported post procedure (combined retrograde urethrogram and antegrade cystourethrogram) fever, which needed another 5 days antibiotic treatment. Conclusion: Single dose of Silodosin before antegrade cystourethrogram conferred a statistically significant increase in opening the bladder outlet inpelvic fracture urethral distraction defectpatients. Bangladesh Crit Care J September 2024; 12 (2): 138-144